2021
DOI: 10.1210/jendso/bvab085
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Likely Pathogenic MAX Germline Variant in a Patient With Unilateral Pheochromocytoma

Abstract: Objective Inherited MAX gene pathogenic variants (PVs) increase risk for pheochromocytomas (PCCs) and/or paragangliomas (PGLs) in adults and children. There is little clinical experience with such mutations. This report highlights an important approach. Methods Clinical assessment, including blood chemistry, imaging studies, and genetic testing were performed. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Among 499 studies, 213 articles reported variants related to PPGLs and 16 papers reported MAX variants. We summarized the characteristics of the cases with PPGLs in MAX variants [ 5 , 15 , 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] ( Supplementary Table S1 ). Combining data from the 16 reports in MAX variants revealed that 42/71 cases (59.2%) had bilateral PCCs, 9/59 cases (8.5%) had PGLs, and 31/70 cases (44.3%) had an apparent family history of PPGLs.…”
Section: Discussionmentioning
confidence: 99%
“…Among 499 studies, 213 articles reported variants related to PPGLs and 16 papers reported MAX variants. We summarized the characteristics of the cases with PPGLs in MAX variants [ 5 , 15 , 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] ( Supplementary Table S1 ). Combining data from the 16 reports in MAX variants revealed that 42/71 cases (59.2%) had bilateral PCCs, 9/59 cases (8.5%) had PGLs, and 31/70 cases (44.3%) had an apparent family history of PPGLs.…”
Section: Discussionmentioning
confidence: 99%